2017
DOI: 10.1186/s40168-017-0347-6
|View full text |Cite
|
Sign up to set email alerts
|

Microbes and associated soluble and volatile chemicals on periodically wet household surfaces

Abstract: Background: Microorganisms influence the chemical milieu of their environment, and chemical metabolites can affect ecological processes. In built environments, where people spend the majority of their time, very little is known about how surface-borne microorganisms influence the chemistry of the indoor spaces. Here, we applied multidisciplinary approaches to investigate aspects of chemical microbiology in a house.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 82 publications
3
58
0
Order By: Relevance
“…Some seasonal difference was observed at this house for surface microbial biomass. As reported by Adams et al, who sampled periodically wet surfaces (including the kitchen sink) in the studied house, greater biomass was detected in the summer campaign than during the winter campaign.…”
Section: Resultssupporting
confidence: 75%
“…Some seasonal difference was observed at this house for surface microbial biomass. As reported by Adams et al, who sampled periodically wet surfaces (including the kitchen sink) in the studied house, greater biomass was detected in the summer campaign than during the winter campaign.…”
Section: Resultssupporting
confidence: 75%
“…[1][2][3][4] These manufactured compounds exist alongside a wide range of naturally occurring and chemically formed SVOCs 2,5 and water-soluble gases 6 as a result of cooking, the use and chemical transformation of consumer products, microbial processes, 7 and volatilization of particulate matter. [1][2][3][4] These manufactured compounds exist alongside a wide range of naturally occurring and chemically formed SVOCs 2,5 and water-soluble gases 6 as a result of cooking, the use and chemical transformation of consumer products, microbial processes, 7 and volatilization of particulate matter.…”
Section: Introductionmentioning
confidence: 99%
“…For example, urine-and fecesassociated bacteria have been shown to be more common on toilet seats and toilet handles than on other surfaces [53]; bacteria associated with fresh produce have been shown to be more common on kitchen countertops and inside refrigerators [54]; and bacteria associated with leaves and soil have been shown to be more common on the interior and exterior trim of doors that open to the outside than other (more interior) home surface locations [55]. Conversely, on surfaces that frequently have high moisture levels, such as those in bathrooms and kitchens (e.g., shower curtains, sinks, and countertops), rich microbial biofilms can form community assemblages that closely resemble those found in plumbing systems and water reservoirs [56][57][58]. Investigating differences both within and between homes, Lax et al (2014) demonstrated that bacterial communities on different surfaces in an individual home showed strong similarities for some surfaces (e.g., kitchen floors were similar to bedroom floors and both were similar to human feet; and kitchen light switches were similar to the front doorknob, which were also similar to occupants' hands) but not for others (e.g., kitchen countertops and human noses were distinct from doorknobs) [3••].…”
Section: Microbial Community Ecology On Fomite Surfacesmentioning
confidence: 99%